The reasons for the establishment of the Health psychology in Latvia - Mārtinsone, Kristīne; Freimane, Gunta; Mihailova, Sandra; Mihailovs, Jānis Ivans (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Health Psychology, based on biopsychosocial approach, addresses the issues of individual, group and society's physical, social and mental health. Today, in Europe and the U.S., it has been defined as one of the branches of psychology. Also, it has started in positioning in Latvia. This paper discusses the necessity of establishing and development of the field and education of health psychology in Latvia, clarifies the meaning and the framework of the health psychology, as well as offers a description of the scope of specialists’ activity and the tendencies of research in this field.